Study on Single-Event Transient Hardness of Semi-Enclosed Gate NMOS - Zhuoxiang Wang; Gang Li; Minghua Tang (Applied Sciences)
Based on the simulation software, single-event transient (SET) simulations were conducted on semi-enclosed gate NMOS devices. The simulation involved bombarding the semi-enclosed gate NMOS devices with heavy ions under specific conditions. A comparative analysis was conducted to evaluate the single-event transient tolerance of traditional NMOS and semi-enclosed gate NMOS. Simulation curves from transient to steady-state states under different Linear Energy Transfer (LET) values, as well as potential distribution and current density distribution maps following heavy ion bombardment, were analyzed. Furthermore, single-event transient simulations were carried out on inverters composed of both NMOS types, with subsequent analysis. The results ultimately demonstrate that the semi-enclosed gate NMOS exhibits superior single-event transient tolerance compared to conventional NMOS.